Strategi Komunikasi Pemasaran “OPPO” Dalam Meningkatkan Penjualan Produk (Studi Pada Toko Erafone Ciputat – Tangerang Selatan) - Hanif, Muhammad; Ajimat, Ajimat (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to find out future strategies to increase sales. The analysis used in this research is SWOT analysis. This research method uses descriptive qualitative research. In this analysis it is known that the Ciputat Branch of the Erafone Store is in quadrant I, this position indicates a company that is strong and has opportunities, so the appropriate strategy to implement is SO, namely the company optimizes its strengths to take advantage of existing opportunities by paying attention to all possible threats from competitors in the market. . SO Strategy steps that need to be given more attention are improving product quality, increasing product diversity, and being more responsive to customer demand. The Ciputat Branch of the Erafone Store can increase existing opportunities by taking advantage of the economy which is starting to grow steadily, the large number of people who are looking for cellphones because they are needed to enter certain locations, and the large number of young and old people who are interested in cellphones.